Hantavirus inhibits TRAIL-mediated killing of infected cells by downregulating Death Receptor 5 - Solà-Riera, Carles; Gupta, Shawon (Cell reports, 2019)
Cytotoxic lymphocytes normally kill virus-infected cells by apoptosis induction. Cytotoxic granule-dependent apoptosis induction engages the intrinsic apoptosis pathway, whereas death receptor (DR)-dependent apoptosis triggers the extrinsic apoptosis pathway. Hantaviruses, single-stranded RNA viruses of the order Bunyavirales, induce strong cytotoxic lymphocyte responses in infected humans. Cytotoxic lymphocytes, however, are largely incapable of eradicating hantavirus-infected cells. Here, we show that the prototypic hantavirus, Hantaan virus (HTNV), induces TRAIL production but strongly inhibits TRAIL-mediated extrinsic apoptosis induction in infected cells by downregulating DR5 cell surface expression. Mechanistic analyses revealed that HTNV triggers both 26S proteasome-dependent degradation of DR5 through direct ubiquitination of DR5 and hampers DR5 transport to the cell surface. These results corroborate earlier findings, demonstrating that hantavirus also inhibits cytotoxic cell granule-dependent apoptosis induction. Together, these findings show that HTNV counteracts intrinsic and extrinsic apoptosis induction pathways, providing a defense mechanism utilized by hantaviruses to inhibit cytotoxic cell-mediated eradication of infected cells.